1999
DOI: 10.1002/(sici)1097-4628(19990118)71:3<387::aid-app4>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphazene membranes. III. Solid-state characterization and properties of sulfonated poly[bis(3-methylphenoxy)phosphazene]

Abstract: Poly[bis(3-methylphenoxy)phosphazene] was sulfonated in a solution with SO 3 and solution-cast into 100 -200-m-thick membranes from N,N-dimethylacetamide. The degree of polymer sulfonation was easily controlled and water-insoluble membranes were fabricated with an ion-exchange capacity (IEC) as high as 2.1 mmol/g. For water-insoluble polymers, there was no evidence of polyphosphazene degradation during sulfonation. The glass transition temperature varied from Ϫ28°C for the base polymer to Ϫ10°C for a sulfonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 17 publications
2
43
0
Order By: Relevance
“…4. As it was reported for several sulfonated polymers [35,[37][38][39], the wateruptake by the sulfonated polyamides increases with the content of ionic groups in the polymer backbone. Fig.…”
Section: Water-uptake and Ion Exchange Capacitysupporting
confidence: 60%
“…4. As it was reported for several sulfonated polymers [35,[37][38][39], the wateruptake by the sulfonated polyamides increases with the content of ionic groups in the polymer backbone. Fig.…”
Section: Water-uptake and Ion Exchange Capacitysupporting
confidence: 60%
“…Sulfonated poly͑ary-loxyphosphazenes͒ have been investigated as fuel cell membranes by Pintauro and co-workers. [14][15][16] Proton conductivities of the sulfonated poly͑aryloxyphosphazene͒ membranes were about half that of Nafion 117 ͑if the ion exchange capacities of both membranes are similar͒, however, the methanol diffusion coefficients for these membranes were almost an order of magnitude lower than those measured for Nafion. Improvements to the mechanical properties of these membranes were obtained by blending with poly͑vinylidene fluoride͒ ͑PVDF͒.…”
mentioning
confidence: 85%
“…In the case of sulfonated P3MPP, Tang and co-workers [21] have reported that diffusion coefficients at 251C for methanol concentrations between 1.0 and 5.0 M were in the range 8.0 Â 10 À8 to 4.0 Â 10 À7 cm 2 /s. These are significantly lower than reported for Nafion and therefore offer promise for DMFC applications.…”
Section: Proton-exchange Membranesmentioning
confidence: 99%
“…Several polyphosphazenes have been proposed for use in DMPCs, due to their low methanol crossover compared to Nafion. These include sulfonated alkyl group-substituted polyphosphazenes based on poly[bis(phenoxy)phosphazenes] (5) [21][22][23], such as sulfonated poly[(3-methylphenoxy)(phenoxy)phosphazene] (P3MPP) (6) and sulfonated poly[bis(3-methylphenoxy)phosphazene] (7) (Chart 2). Phosphonated polyphosphazenes [24] have also been used as described below.…”
Section: Proton-exchange Membranesmentioning
confidence: 99%